Insentif Pajak, Kesadaran Wajib Pajak, Sosialisasi Pajak dan Kepatuhan Wajib Pajak Usaha Mikro Kecil dan Menegah - Indah Febriani, Ni Putu; Noviari, Naniek (E-Jurnal Akuntansi; Vol 33 No 7 (2023), 2023)
The research aims to determine the effect of tax incentives, taxpayer awareness, and tax socialization on taxpayer compliance of Micro, Small and Medium Enterprises (MSMEs). The research was conducted at the East Denpasar Pratama Tax Service Office (KPP) with a total sample of 98 respondents as individual MSME taxpayers. The data analysis technique used in this research is Multiple Linear Regression Analysis. Based on the results of the analysis it was found that tax incentives, taxpayer awareness, and tax socialization have a positive effect on taxpayer compliance. This shows that by providing tax incentives that are put to good use, adequate awareness of taxpayers, and holding regular tax socialization, the higher the level of compliance of MSME taxpayers. Keywords: Tax Incentives; Taxpayer Awareness; Socialization; Compliance